2022
DOI: 10.1149/1945-7111/ac6448
|View full text |Cite
|
Sign up to set email alerts
|

Imidazolium-Type Anion Exchange Membranes for Improved Organic Acid Transport and Permselectivity in Electrodialysis

Abstract: Most commercial anion exchange membranes (AEMs) deploy quaternary ammonium moieties. Alternative cation moieties have been explored in AEMs for fuel cells, but there are no studies focused on examining alternative tethered cations in AEMs for ionic separations – such as organic acid anion transport via electrodialysis. H-cell and conductivity experiments demonstrate that tethered benzyl 1-methyl imidazolium groups in polysulfone AEMs enhance lactate conductivity by 49% and improved lactate anion flux by 24x wh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(36 citation statements)
references
References 54 publications
3
33
0
Order By: Relevance
“…Because the equilibrium partitioning coefficient difference for p-coumarate between QIPSf and QAPSf is not commensurate with the permeability coefficient differences, we inferred that the p-coumarate diffusivity was greater in QIPSf over QAPSf as permeability is the product of the partitioning coefficient and the diffusion coefficient. This observation was also observed in our previous work 27 for a lactate (i.e., QIPSf AEMs promoted lactate transport when compared to QAPSf AEMs). Because QIPSf enhances pcoumarate permeability, we used this material as a AEM and resin wafer binder in the new MWAs.…”
Section: Manufacturing Of Membrane-laminated Ionomer Binder Resin Waf...supporting
confidence: 88%
See 4 more Smart Citations
“…Because the equilibrium partitioning coefficient difference for p-coumarate between QIPSf and QAPSf is not commensurate with the permeability coefficient differences, we inferred that the p-coumarate diffusivity was greater in QIPSf over QAPSf as permeability is the product of the partitioning coefficient and the diffusion coefficient. This observation was also observed in our previous work 27 for a lactate (i.e., QIPSf AEMs promoted lactate transport when compared to QAPSf AEMs). Because QIPSf enhances pcoumarate permeability, we used this material as a AEM and resin wafer binder in the new MWAs.…”
Section: Manufacturing Of Membrane-laminated Ionomer Binder Resin Waf...supporting
confidence: 88%
“…The previous static studies of QIPSF and QAPSF with lactate anions showed that lactate anions bind closer to the imidazolium cations when compared to the quaternary ammonium cation. 27 Similar observations are seen with the p-coumarate anion when considering the same interaction sites (labeled carbons in Figure 8) of the imidazolium group and ammonium groups. The radial distribution function, g(r), calculated between the labeled carbon in each head group in each case with the carbonyl carbon of p-coumarate (Figure 8) shows that p-coumarate association with imidazolium head groups is prominent due to the larger peak height for pcoumarate−imidazolium compared to p-coumarate−ammonium.…”
Section: Manufacturing Of Membrane-laminated Ionomer Binder Resin Waf...supporting
confidence: 65%
See 3 more Smart Citations